2021
DOI: 10.1111/cfs.12886
|View full text |Cite
|
Sign up to set email alerts
|

Dating violence in adolescents in residential care: Frequency and associated factors

Abstract: Prevalence of dating violence (DV) is increasing, so the detailed study of the related factors can help to intervene in it more specifically. This study had three goals: to analyse the frequency of DV; to explore the differences between the frequency of perpetration and victimization of DV and sexist attitudes, antisocial and criminal behaviours and personal adjustment and to identify predictor variables of the frequency of DV. The sample consisted of 271 adolescents in residential care (54.6% boys and 45.4% g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…First, the results revealed the existence of victimization in adolescent dating relationships (32.8% of the sample), in line with previous studies that have examined the prevalence of this phenomenon (Viejo et al, 2016;Marcos et al, 2022). This finding is consistent with the need to emphasize that this type of victimization is a serious social and public health problem (Dosil et al, 2022;Soller et al, 2020); which should be addressed in the educational, social and health fields among the younger population, to: a) minimise the mismatch between the perception of objective victimization and subjective victimization; b) reduce violent behaviours in dating relationships; c) raise awareness of the severity of violent behaviours that occur in interpersonal relationships.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First, the results revealed the existence of victimization in adolescent dating relationships (32.8% of the sample), in line with previous studies that have examined the prevalence of this phenomenon (Viejo et al, 2016;Marcos et al, 2022). This finding is consistent with the need to emphasize that this type of victimization is a serious social and public health problem (Dosil et al, 2022;Soller et al, 2020); which should be addressed in the educational, social and health fields among the younger population, to: a) minimise the mismatch between the perception of objective victimization and subjective victimization; b) reduce violent behaviours in dating relationships; c) raise awareness of the severity of violent behaviours that occur in interpersonal relationships.…”
Section: Discussionsupporting
confidence: 83%
“…Dating violence (DV) is a worldwide serious social and public health problem (Dosil et al, 2022;Soller et al, 2020;Taylor & Mumford, 2016), with a prevalence rate ranging from 23% to 30% (Viejo et al, 2016), despite of victimization rates vary depending on the characteristics of the samples (i.e., gender, age, race/ethnicity, country, measurement instruments) (Exner-Cortens et al, 2021;Shamu et al, 2016). In this regard, in a meta-analytic review, Wincentak et al (2017) found that one in ten adolescents reported victimization in their dating relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding offline dating violence, recent studies indicated that 59.2% of young people with an average age of 19 had experienced some form of violence (Hébert et al 2019). Some studies suggest that older adolescents are at higher risk for dating violence (Dosil-Santamaria et al 2022), while others point to a higher risk of victimization at younger ages, particularly in girls (Bonomi et al 2012), and less violent behavior (Pacheco et al 2017;Smith et al 2003). However, it is important to focus on the age rate of the studies.…”
Section: Prevalence Of Offline and Online Violence By Sex And Agementioning
confidence: 99%
“…Children and young people living in residential care are at a much greater risk of experiencing sexual abuse and dating violence than those living in the general community (Allroggen et al, 2018; Dosil et al, 2022). However, those living in home‐based (foster) care experience sexual abuse at about the same rate as those in the general population (Euser, et al, 2013)—approximately 20% of girls and 8% of boys before the age of 15 (Pereda et al, 2009).…”
Section: Introductionmentioning
confidence: 99%